The psychological impact of the American war on Iraqi children (2003-2010) - Laouidji, karima; Senouci Meberbeche, Faiza (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
War, as a destabilizing force, is considered to be among the greatest dangers that threaten the physical and the mental wellbeing of civilians everywhere. The main focus of the present study is to shed light on the suffering of Iraqi children by the time of United States led- invasion. The American invasion of Iraq was initiated in March 2003 and triggered a wave of violence and turmoil in the country, in which children were major victims of this war due to the negative effects of this armed conflict on their lives. Memories of bombing and killing were likely to affect the mental wellbeing of children at the moment and even in the future as it had a long-term effect. The suffering of Iraqi children was not a new thing as it dated back to different successive events: The Iraq-Iran war (1980-1988), the Gulf War (1990-1991), the United Nation's sanctions on Iraq (1990) and finally the American war (2003). The aim of this paper is to understand how the war deprived children from their basic needs, supportive environment, educational and other psychological resources that promote their development, this situation led to a significant psychological harm due to the persistent threat of war and the lack of social security. Psychological problems like depression, trauma and mental disorder became part of the life of Iraqi children.